Fundamental physics and other applications using nonneutral plasma - G. Maero; E. D. Hunter; D. J. Murtagh; E. V. Stenson (Advances in Physics: X)
During the last fifty years, nonneutral plasma physics has developed into a definite subfield of basic research, whose main focus has been on the collective properties of systems comprising many charged particles, such as nonlinear dynamics, equilibrium, and stability. And yet, aided by the development of suitable electromagnetic traps and ever-evolving manipulation and detection techniques, this field has branched towards many other applications well beyond the scope of plasma physics, with a notable example being low-energy antimatter. This review presents a selection of recent developments and perspectives in nonneutral plasmas, covering both basic plasma physics phenomena, which are also relevant to the nonlinear dynamics of two-dimensional fluids, as well as the advances they have enabled in the progress of antihydrogen formation, positron and positronium physics, and the creation of exotic samples such as pair plasmas.